X elevado a 3 menos 1
Soluções para a tarefa
Respondido por
2
Primeiro nós declaramos uma igualdade: x³ - 1 = 0
Após, resolvemos essa equação do 3° grau:
x³ - 1 = 0
x³ = 1
x =![\sqrt[3]{1} \sqrt[3]{1}](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7B1%7D+)
x = 1
Após, resolvemos essa equação do 3° grau:
x³ - 1 = 0
x³ = 1
x =
x = 1
Perguntas interessantes
Física,
11 meses atrás
Química,
11 meses atrás
Matemática,
11 meses atrás
Administração,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás